A Comparative Approach to the Problem of Evil from a Theological and Philosophical Perspective - Metin Özdemir (ULUM, 2018)
The problem of evil is the common problem of both philosophy and theology. Philosophers and kalām scholars have developed a theodicy/defense of divine justice that is in keeping with their understanding of religion, paradigms and methodologies. They have tried to explain and make sense of the evil in the world in accordance with their theories of creation. For this reason, both sides show serious differences in both metaphysical and moral evil. Philosophers have drifted away from rational thought on the topic of metaphysical evil as they have stuck to emanation theory based on fictional assumptions, yet have taken an exceptionally rational path towards moral evil. Kalām scholars, on the other hand, have never been able to disentangle themselves from turning both the matter of natural and moral evil into a metaphysical problem. The truth is that this problem will be more resolvable when it is evaluated together with the laws of universe, testing process and the belief of hereafter. In order to be able to see their point of departure and rational basis in this subject, we have tried to present this article in a comparative manner with the main lines.